Qualitative and Quantitative Phytochemical Analysis of Ononis Hairy Root Cultures - Gampe, Nóra; Szakács, Zoltán; Darcsi, András; Boldizsár, Imre; Szőke, Éva; Kuzovkina, Inna; Kursinszki, László; Béni, Szabolcs (Frontiers in Plant Science, 2021)
Hairy root cultures are genetically and biochemically stable, and they regularly possess the same or better biosynthetic capabilities for specialized (secondary) metabolite production compared to the intact plant. Ononis species are well-known herbal remedies in ethnopharmacology, and rich sources of isoflavonoids. Besides isoflavones, less prevalent isoflavanones and pterocarpans with valuable biological effects can be found in Ononis species as well. As these plants are only collected but not cultivated, biotechnological methods could play a role in the larger scale extraction of Ononis isoflavonoids. Regarding this information, we aimed to establish Ononis spinosa and O. arvensis hairy root cultures (HRCs), analyze the isoflavonoid profile of hairy root cultures qualitatively and quantitatively, in order to define their capacity to produce biologically valuable isoflavonoids. During the qualitative description, beside isoflavonoids, two new phenolic lactones, namely bulatlactone 2”-O-β-D-glucoside and ononilactone were isolated, and their structure was characterized for the first time. Altogether 29 compounds were identified by the means of UPLC-Orbitrap-MS/MS. Based on UHPLC-UV-DAD measurements, the isoflavonoid spectrum of the Ononis HRCs differed markedly from wild-grown samples, as they produce a limited range of the scaffolds. The most abundant compounds in the HRCs were medicarpin glucoside and sativanone glucoside. The overall isoflavonoid production of the cultures were comparable to wild-grown O. arvensis, and approximately twice as high as in wild-grown O. spinosa samples. As the overall content of wild-grown samples include more isoflavonoid derivatives, the HRCs contain structurally less divergent isoflavonoids but in higher quantity.